PERAN ORANGTUA DALAM MENDUKUNG PROGRAM SEKOLAH MEMBENTUK GENERASI YANG BERIMAN, KREATIF DAN BERBUDAYA - Heppy Wulandari; Afifatu Rohmawati (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Early childhood education (ECE) is an important foundation for individual growth, ethics, and creative abilities. Schools and families must work together to support education at an early stage, especially the role of parents in creating an environment that supports children's exploration. This study was conducted using a qualitative methodology with a case study at Al Madani Kindergarten in Banjarejo, Pagelaran, Malang Regency. Data were collected through direct observation at the school and in-depth interviews with teachers and parents. The results showed that active parental involvement strengthened the home-school relationship and instilled cultural and spiritual values ​​in children's lives. Children enjoyed their exploration in a pleasant home environment, which had a positive impact on their cognitive, emotional, and social development. These results show how important it is for schools, parents, and communities to work together to create a comprehensive educational ecosystem. This ecosystem is very important to support children's development from an early age and build a strong foundation for their future. Keywords: Early Childhood Education; Role of Schools; Parental Involvement; Cultural; Spiritual; Creativity Values